Enhancing Elementary Students’ Engagement and Understanding through Generative AI Integration in Digital Learning Environments - Sakinah; Rinaldi, Cherry; Khamidi, Amrozi; Amalia, Kaniati; Haq, Mohammad Syahidul (Journal of Innovation and Research in Primary Education, 2025)
This study investigates the effectiveness of integrating generative Artificial Intelligence (AI) into digital learning environments in enhancing engagement and understanding among elementary school students. Employing a quasi-experimental design with pretest-posttest control groups, the research involved 60 fourth- and fifth-grade students at Sekolah Indonesia Riyadh. The experimental group received instruction integrated with generative AI tools, such as ChatGPT, over six weeks, while the control group engaged in conventional digital learning without AI support. Student engagement was measured through validated questionnaires capturing cognitive, affective, and behavioral dimensions, and comprehension was assessed using standardized tests. Results revealed statistically significant improvements in both engagement and understanding within the experimental group compared to the control group. The use of generative AI facilitated personalized, responsive learning, enabling students to interact meaningfully with content, clarify concepts in real time, and maintain higher levels of motivation and participation. These findings underscore the potential of generative AI as an effective pedagogical instrument in elementary education. The study further emphasizes the importance of teacher facilitation and institutional readiness in ensuring successful AI integration. Although limited by duration and context, this research provides empirical evidence supporting the thoughtful adoption of generative AI in education. Future studies are recommended to explore long-term impacts and broader implementation across diverse educational settings. The study concludes that generative AI, when applied within pedagogically grounded frameworks, can significantly enhance the quality of digital learning experiences for young learners.